Hermetia illucens (L.) larvae as chicken manure management tool for circular economy. (20th July 2020) - Bortolini, Sara; Macavei, Laura Ioana; Saadoun, Jasmine Hadj; Foca, Giorgia; Ulrici, Alessandro; Bernini, Fabrizio; Malferrari, Daniele; Setti, Leonardo; Ronga, Domenico; Maistrello, Lara
Abstract: The increased request for poultry meat and eggs of a rising human population requires more efficient and cleaner methods to manage increasing quantities of chicken manure. The black soldier fly Hermetia illucens is known as an efficient bio-converter of organic waste in proteins and fats, with the advantage that the larval frass is supposed to have compost-like properties. In the view to identify the operating conditions for the sustainable management and valorization of livestock waste at a pre-industrial scale, this study is aimed at: i) optimizing the growth of H. illucens on a mixture of chicken manure, chabazite and water; ii) assessing the soil amendment properties of the larval frass obtained from the optimized mixture. Preliminary trials allowed defining the basic rearing conditions in terms of temperature and substrate components. A mixture design based on a special cubic model allowed identifying the best mixture for H. illucens larvae growth, which consists in 34.5% chicken manure, 58.3% water and 7.2% coarse chabazite. This mix led to about 86% of alive prepupae weighting 90 mg on average, and to a reduction of the initial substrate amount by more than 75%. The larval frass obtained from this mixture showed soil improver properties, suggesting its use to supply the common peat based growing media for potted baby-leaf lettuce production. Overall, H. illucens larvae have proved to be a useful tool to favor a more sustainable management of chicken manure by strongly reducing its amount and closing its recovery cycle obtaining high value products for agricultural purposes. Highlights: Valorization of poultry manure with chabazite can be achieved using BSF larvae. Optimal mixtures maximizing BSF performance and substrate reduction identified. Coarse chabazite is compatible with BSF larval growth, if less than 8%. BSF larval frass demonstrated soil improver features on baby-leaf lettuce. Attainment of operating conditions to rear BSF larvae in a pilot plant.